2017
DOI: 10.1038/srep46559
|View full text |Cite
|
Sign up to set email alerts
|

Long term stability and infectivity of herpesviruses in water

Abstract: For viruses to utilize environmental vectors (hard surfaces, soil, water) for transmission, physical and chemical stability is a prerequisite. There are many factors including pH, salinity, temperature, and turbidity that are known to contribute to the ability of viruses to persist in water. Equine herpesvirus type-1 (EHV-1) is a pathogenic alphaherpesvirus associated with domestic horses and wild equids. EHV-1 and recombinants of EHV-1 and EHV-9 are able to cause infections in non-equid animal species, partic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 32 publications
0
31
0
1
Order By: Relevance
“…However, it was shown that EHV‐1 can remain stable and infectious for over a week and up to 3 weeks in water under different conditions of salinity, pH, temperature and turbidity in controlled in vitro experiments (Dayaram et al . ).…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…However, it was shown that EHV‐1 can remain stable and infectious for over a week and up to 3 weeks in water under different conditions of salinity, pH, temperature and turbidity in controlled in vitro experiments (Dayaram et al . ).…”
Section: Introductionmentioning
confidence: 97%
“…Direct contact with EHV-1-infected aborted fetuses, placental tissues or fomites contaminated by respiratory secretions may serve as a source of infection although the viruses are reported to be relatively short-lived in the environment (Reed & Toribio 2004;Harless & Pusterla 2006). However, it was shown that EHV-1 can remain stable and infectious for over a week and up to 3 weeks in water under different conditions of salinity, pH, temperature and turbidity in controlled in vitro experiments (Dayaram et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Livestock grazing is typically constrained to pastures close to water, thereby often reducing water and pasture accessible to wildlife 8,[11][12][13][14] . Shared use of waterpoints harbours the risk of disease transmission between livestock and wildlife 15,16 . Finally, diversion of water for irrigation results in habitat conversion and when associated with fencing tends to block access to water by wildlife altogether.…”
mentioning
confidence: 99%
“…Transmission and epidemiology: Virus transmission occurs through direct contact between horses, fomites, infectious aerosols and/or indirectly by humans. A recent study demonstrating the survival of EHV-1 in water strongly suggests a potential new way of transmission [30]. EHV-1 causes frequent outbreaks of abortion and myeloencephalopathy worldwide, even in vaccinated horses (Figure 4).…”
Section: Equid Herpesvirusesmentioning
confidence: 97%